Conceptual structuring of corporate legal risk: a doctrinal and hermeneutic analysis - Sánchez Sánchez , Juan Diego (Scientific journal of social studies, 2024)
The paper focuses on a conceptual and technical analysis regarding the structuring and conceptualization of business legal risk, this from a corporate perspective, but with a link to its management from the legal area, considering for these purposes the variables and factors that creates the concept and its practical use in companies. A hermeneutical analysis of the different convergent theories in the epistemological structuring of the concept of the legal-business risk variable is detailed, addressing in turn the branches of Law and their link to the management of lucrative business operations.